Social Comparisons in Wage Delegation: Experimental Evidence - Gary Charness; Ramón Cobo-Reyes; Juan A. Lacomba; Francisco Lagos; José María Pérez (Institute for the Study of Labor (IZA), 2013)
This article examines whether social comparisons have behavioral effects on workers' performance when a firm can choose workers' wages or let them choose their own. Firms can delegate the wage decision to neither, one or both workers in the firm. We vary the information workers receive, finding that social comparisons concerning both wages and decision rights affect workers' performance. Moreover, the relative effect of discrimination in relation to decision rights is larger than in relation to wage. We find these treatment effects with both stated effort and a real-effort task, suggesting that both approaches may yield similar results.
Keywords: C91; 330; delegation; gift-exchange; experiment